Safety and effectiveness of ustekinumab for induction of remission in patients with Crohn's disease: A multicenter Israeli study. Issue 4 (May 2020) - Bar-Gil Shitrit, Ariella; Ben-Ya'acov, Ami; Siterman, Matan; Waterman, Matti; Hirsh, Ayal; Schwartz, Doron; Zittan, Eran; Adler, Yehonatan; Koslowsky, Benjamin; Avni-Biron, Irit; Chowers, Yehuda; Ron, Yulia; et al.
Introduction: Ustekinumab is an effective treatment of Crohn's disease (CD). Real-world data addressing the efficacy and safety of ustekinumab are scarce. Aim: Our aim was to assess the safety and efficacy of ustekinumab in a large national patient cohort. Methods: A prospective multicenter study, in which we followed patients with active CD treated with ustekinumab for 24 weeks. Induction dose was intravenous ranging from 260 to 520 mg, according to body weight, followed by 90 mg doses given subcutaneously every 8 weeks. Clinical response was defined as a reduction of at least 1 severity category, as defined by Harvey–Bradshaw index (HBI). Patients with HBI < 5 were considered to be in clinical remission. Patients who stopped needing steroids at week 24 were defined as being in steroid-free clinical remission. Results: A total of 106 CD patients from eight Israeli centers were included. All patients were previously exposed to at least one biological agent. Our cohort consisted of 65 (61.3%) females. Mean age was 41 ± 14 years with an average disease duration of 12.2 ± 8 years. A total of 96 (90.5%) patients continued treatment throughout week 24. Clinical response was observed in 52% of these patients with mean HBI reduction from 8.34 ± 3.8 to 6.8 ± 4.4 at week 24 ( p = 0.001). Clinical remission was achieved in 33 patients (31.1%). Moreover, the number of patients requiring steroid treatment was reduced by 66% at week 24. Out of 106 patients, 11 patients (10.4%) discontinued treatment: 3 due to adverse events (2.8%), 7 due to a lack of response, and 1 who was lost to follow-up. Following 24 weeks of treatment, 15 patients reported minor adverse events. Conclusions: In a large real-world Israeli cohort of non-naïve-to-biological-treatment CD patients, ustekinumab was effective and safe in induction of clinical remission with a significant reduction in the number of patients requiring steroid treatment.